A Review of Performance Evaluation Measures for Actively-Managed Portfolios - Hsieh, Heng-Hsing (Journal of Economics and Behavioral Studies, 2013)
In the recognition that investment management is an on-going process, the performance of actively-managed portfolios need to be monitored and evaluated to ensure that funds under management are efficiently invested in order to satisfy the mandate specified in the policy statement. This paper discusses the primary performance evaluation techniques used to measure a portfolio’s basic risk and return characteristics, risk-adjusted performance, performance attribution and market timing ability. It is concluded that the Treynor measure is more suitable for evaluating portfolios that are constituents of a broader portfolio, while the information ratio is useful for evaluating hedge funds with an absolute return objective. Although the Sharpe ratio and M-squared arrive at the same evaluation result, M-squared provides a direct comparison between the portfolio and the benchmark. With regard to the analysis of portfolio performance attribution, it is found that the return-based multifactor model of Sharpe (1992) is not suitable for analyzing the performance of hedge funds that engage in short-selling, leverage and derivatives. Additional factors generated by factor analysis could be used as factors in the extended model of Sharpe (1992) to analyze hedge fund return attributions. Finally, the Treynor and Mazuy (1966) model and the Henriksson and Merton (1981) model essentially distinguish the market timing ability from the security selection ability of the portfolio manager.